Crosstalk between melatonin and reactive oxygen species in fruits and vegetables post-harvest preservation: An update - Li, Na; Zhai, Kefeng; Yin, Qin; Gu, Quan; Zhang, Xingtao; Melencion, Merced G.; Chen, Ziping (Frontiers in Nutrition, 2023)
Fruits and vegetables contain numerous nutrients, such as vitamins, minerals, phenolic compounds, and dietary fibres. They reduce the incidence of cardiovascular diseases and the risk of certain chronic diseases, and improve the antioxidant and anti-inflammatory capacity. Moreover, melatonin was found in various fruits and vegetables species. Melatonin acts as a multifunctional compound to participate in various physiological processes. In recent years, many advances have been found that melatonin is also appraised as a key modulator on the fruits and vegetables post-harvest preservation. Fruits and vegetables post-harvest usually elicit reactive oxygen species (ROS) generation and accumulation. Excess ROS stimulate cell damage, protein structure destruction, and tissue aging, and thereby reducing their quality. Numerous studies find that exogenous application of melatonin modulates ROS homeostasis by regulating the antioxidant enzymes and non-enzymatic antioxidants systems. Further evidences reveal that melatonin often interacts with hormones and other signaling molecules, such as ROS, nitric oxide (NO), hydrogen sulfide (H2S), and etc. Among these ‘new’ molecules, a comprehensive outline of melatonin-regulated redox homeostasis and interaction of melatonin and ROS is provided in fruits and vegetables post-harvest preservation in this review, which provide reference for future complicated integration of both melatonin and ROS as signal molecules.